2022
DOI: 10.1049/mna2.12113
|View full text |Cite
|
Sign up to set email alerts
|

Facile hydrothermal synthesis CuO microflowers for non‐enzymatic glucose sensors

Abstract: With diabetes mellitus increasing, developing non-enzymatic glucose sensors to replace enzyme-based sensors has become more urgent, owing to its intrinsic disadvantages of enzymes. Herein, CuO microflowers were successfully synthesized through a green hydrothermal method with no template or surfactant. X-ray diffraction, X-ray photoelectron spectroscopy, scanning electron microscopy and transmission electron microscopy were used to study the crystalline structure, elemental composition and morphology of the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…The sensor response showed a very small response loss, lower than 5% after this period, confirming the excellent stability of the copper thin film deposited on the ITO electrode and its potential for further implementations in industrial and analytical applications. These results demonstrate the good electrocatalytic properties of the sensor with a low limit of detection and excellent sensitivity, better than previous values reported in the literature [19,22,32,[34][35][36][37][38][39][40][41][42][43][44][45] (see Table 1). The effect of other similar sugars (sucrose, lactose, and fructose) and common reducing agents (uric acid and ascorbic acid) found in biological and analytical matrixes were assessed.…”
Section: Electrochemical Characterization and Sensor Responsesupporting
confidence: 67%
“…The sensor response showed a very small response loss, lower than 5% after this period, confirming the excellent stability of the copper thin film deposited on the ITO electrode and its potential for further implementations in industrial and analytical applications. These results demonstrate the good electrocatalytic properties of the sensor with a low limit of detection and excellent sensitivity, better than previous values reported in the literature [19,22,32,[34][35][36][37][38][39][40][41][42][43][44][45] (see Table 1). The effect of other similar sugars (sucrose, lactose, and fructose) and common reducing agents (uric acid and ascorbic acid) found in biological and analytical matrixes were assessed.…”
Section: Electrochemical Characterization and Sensor Responsesupporting
confidence: 67%
“…The higher the oxidation current was, the higher the number of molecules undergoing the oxidation reaction. As shown in Figure a 1 ,a 2 , the DPVs for ribose on antipodal CCFs exhibited current increases at 0.4–0.6 V, which matched the oxidation potentials for hydroxyls in monosaccharides. , The oxidation current for d -ribose was higher than that for l -ribose on l -CCFs and vice versa on d -CCFs, indicating that the affinity of l -CCFs for d -ribose was higher than that of l -ribose and vice versa for d -CCFs and ribose enantiomers. Voltammograms for the amino acids (Figure b–d and Figure S3) showed that all of the oxidation currents increased at 0.55–0.7 V, which approximately matched the oxidation potential of amidogens in amino acids. , In contrast to the situation for ribose, the oxidation currents for the amino acids with l -configurations were higher than those for the d -configuration on l -CCFs and vice versa for d -CCFs.…”
mentioning
confidence: 58%
“…As shown in Figure 2a 1 ,a 2 , the DPVs for ribose on antipodal CCFs exhibited current increases at 0.4− 0.6 V, which matched the oxidation potentials for hydroxyls in monosaccharides. 42,43 The oxidation current for D-ribose was higher than that for L-ribose on L-CCFs and vice versa on D-CCFs, indicating that the affinity of L-CCFs for D-ribose was higher than that of L-ribose and vice versa for D-CCFs and ribose enantiomers. Voltammograms for the amino acids (Figure 2b−d and Figure S3) showed that all of the oxidation currents increased at 0.55−0.7 V, which approximately matched the oxidation potential of amidogens in amino acids.…”
mentioning
confidence: 98%